\(\left(3,5-4x\right):\frac{22}{3}=75\%\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

18 tháng 4 2019

\(\left(3,5-4x\right):\frac{22}{3}=75\%\)

\(\left(\frac{7}{2}-4x\right):\frac{22}{3}=\frac{3}{4}\)

\(\frac{7}{2}-4x=\frac{3}{4}.\frac{22}{3}\)

\(\frac{7}{2}-4x=\frac{11}{2}\)

\(4x=\frac{7}{2}-\frac{11}{2}\)

\(4x=-2\)

\(x=\left(-2\right):4\)

\(x=\frac{-1}{2}\)

18 tháng 4 2019

\(\left(3,5-4x\right):\frac{22}{3}=75\%\)

\(\left(3,5-4x\right):\frac{22}{3}=\frac{3}{4}\)

\(3,5-4x=\frac{3}{4}.\frac{22}{3}\)

\(3,5-4x=\frac{11}{2}\)

\(4x=3,5-\frac{11}{2}\)

\(4x=-2\)

\(x=-2:4\)

\(x=-\frac{1}{2}\)

#Thiên Mã#

9 tháng 5 2018

(7/2-2x).10/3=22/3

(7/2-2x) = 22/3:10/3

7/2-2x = 11/5

2x = 7/2-11/5

2x = 13/10

x = 13/10:2

x = 13/20

9 tháng 5 2018

\(\left(3,5-2x\right).3\dfrac{1}{3}=\dfrac{22}{3}\\ \left(3,5-2x\right)=\dfrac{22}{3}:\dfrac{10}{3}=\dfrac{22}{3}.\dfrac{3}{10}=\dfrac{11}{5}\\ 2x=\dfrac{7}{2}-\dfrac{11}{5}=\dfrac{13}{10}\\ x=\dfrac{13}{10}:2=\dfrac{13}{10}.\dfrac{1}{2}=\dfrac{13}{20}\)

20 tháng 8 2020

a. 3/7+(-5/2)+(-3/5)

= 3/7-5/2-3/5

=30/70-175/70-42/70

=-145/70-42/70

=-187/70 

b. -8/18-15/27

= -4/9-15/27

= -12/27-15/27

= -27/27

= -1 

c. 4/5-(-2/7)-7/10

=4/5+2/7-7/10

=56/70+20/70-49/70

=76/70-49/70

=27/70

d. 3,5-(-2/7)

=7/2-(-2/7) 

=7/2+2/7

=49/14+4/14

=53/114

20 tháng 8 2020

a. \(\left(\frac{2}{3}\right)^3-\left(\frac{3}{4}\right)^2.\left(-1\right)^5=\frac{8}{27}-\frac{9}{16}.\left(-1\right)=\frac{8}{27}+\frac{9}{16}=\frac{371}{432}\)

b. \(12:\left(\frac{3}{4}-\frac{5}{6}\right)^2=12:\left(-\frac{1}{12}\right)^2=12:\frac{1}{144}=12.144=1728\)

c. \(\frac{7}{22}:\frac{3}{11}+\frac{7}{22}:\frac{4}{11}=\frac{7}{22}.\frac{11}{3}+\frac{7}{22}.\frac{11}{4}=\frac{7}{22}\left(\frac{11}{3}+\frac{11}{4}\right)\)

\(=\frac{7}{22}.\frac{77}{12}=\frac{49}{24}\)

d. \(\frac{12}{35}\left(\frac{7}{4}+\frac{13}{4}\right)-\frac{1}{3}=\frac{12}{35}.5-\frac{1}{3}=\frac{12}{7}-\frac{1}{3}=\frac{29}{21}\)

28 tháng 5 2020

1) \(\left(\frac{7}{8}-\frac{3}{4}\right).1\frac{1}{3}-\frac{2}{7}.\left(3,5\right)^2\)

= \(\frac{1}{8}.\frac{4}{3}-\frac{2}{7}.\frac{49}{4}\) = \(\frac{-10}{3}\)

2) \(\frac{5}{4}:\frac{1}{2}-\frac{3}{4}\) = \(\frac{7}{4}\)

2 tháng 6 2019

Bài 1 : \(a,\left|x-3,5\right|=7,5\)

\(\Rightarrow\orbr{\begin{cases}x-3,5=7,5\\x-3,5=-7,5\end{cases}}\Rightarrow\orbr{\begin{cases}x=11\\x=-4\end{cases}}\)

\(b,\left|x+\frac{3}{4}\right|-\frac{1}{2}=0\)

\(\Rightarrow\left|x+\frac{3}{4}\right|=\frac{1}{2}\)

\(\Rightarrow\orbr{\begin{cases}x+\frac{3}{4}=\frac{1}{2}\\x+\frac{3}{4}=-\frac{1}{2}\end{cases}}\Rightarrow\orbr{\begin{cases}x=-\frac{1}{4}\\x=-\frac{5}{4}\end{cases}}\)

2 tháng 6 2019

\(c,3,6-\left|x-0,4\right|=0\)

\(\Rightarrow\left|x-0,4\right|=3,6\)

\(\Rightarrow\orbr{\begin{cases}x-0,4=3,6\\x-0,4=-3,6\end{cases}}\Rightarrow\orbr{\begin{cases}x=4\\x=-3,2\end{cases}}\)

\(d,\left|x-\frac{1}{2}\right|-\frac{1}{3}=1\)

\(\Rightarrow\left|x-\frac{1}{2}\right|=\frac{4}{3}\)

\(\Rightarrow\orbr{\begin{cases}x-\frac{1}{2}=\frac{4}{3}\\x-\frac{1}{2}=-\frac{4}{3}\end{cases}}\Rightarrow\orbr{\begin{cases}x=\frac{11}{6}\\x=-\frac{5}{6}\end{cases}}\)

13 tháng 6 2020

a, \(-1,8:\left(1-\frac{3}{4}\right)\)

\(=-\frac{9}{5}:\frac{1}{4}\)

\(=-\frac{36}{5}\)

b, \(\left(\frac{7}{8}-\frac{3}{4}\right)\cdot1\frac{1}{3}-\frac{2}{7}\cdot\left(3,5\right)^2\)

\(=\left(\frac{7}{8}-\frac{6}{8}\right)\cdot\frac{4}{3}-\frac{2}{7}\cdot12.25\)

\(=\frac{1}{8}\cdot\frac{4}{3}-\frac{2}{7}\cdot\frac{49}{4}\)

\(=\frac{1}{6}-\frac{7}{2}\)

\(=\frac{1}{6}-\frac{21}{6}\)

\(=-\frac{20}{6}\)

\(=-\frac{10}{3}\)